Approach in managing conflict in a long distance marriage / Hidayatul Sakinah Mohd Zulkifli, Rafeah Saidon and Azhar Abd Aziz - Mohd Zulkifli, Hidayatul Sakinah; Saidon, Rafeah; Abd Aziz, Azhar (Universiti Teknologi MARA, 2022)
Harmony in the household is essential for the well-being of a family institution. Despite this, conflicts are natural occurrences but can negatively influence the family, particularly in households where long-distance marriage is practised. The purpose of this article is to discuss the causes of marital conflict in long-distance marriages and strategies for dealing with it. This qualitative study of five wives and five husbands who practise long-distance marriage were collected using an online questionnaire and purposive sampling. The study revealed that disputes in the households of couples who practise long-distance marriage emerge from a variety of external and internal factors. Internal factors that cause conflict include stress, a lack of communication, limited affection, minimal support, and a lack of trust. While external factors include an intruding third party and financial concerns. Long-distance marriage conflicts can be handled using one's role, middlemen, and authority. Spirituality, encounters, communication, and support systems have been identified as four significant themes in conflict management approaches as shared by the informants. The findings provide benefits in reducing conflicts that occur in the household so that the collapse of the family institution can be avoided by understanding and exercising appropriate conflict management.